IDENTIFIKASI MIKRORGANISME TERBAWA BENIH KEDELAI VARIETAS GALUNGGUNG, WILIS, DAN ANJASMORO - Andree Saylendra; Andy Apriany Fatmawaty (Jurnal Agroekoteknologi, 2010)
ABSTRACTThe objective of this experiment was conducted to identification of seed-borne microorganism that infected or contaminated soybean from Galunggung, Wilis, and Anjasmoro varieties. Soybean seed samples were collected from BB Biogen Cimanggu Bogor. One hundred seeds used by random sampling method as the work sample in seed health testing were obtain from 1000 gram of the sample. Testing method that been used were blotter test and agar test. Bacteria and twelve genera of fungi were found from this experiment. They were Rhizopus, Aspergillus, Fusarium, Alternaria, Culvularia, Mucor, Pythium, Corynespora, Cercospora, Colletotrichum, Phoma, and Pythium.Key words: identification, microorganism, soybean, seed-borne